2006
DOI: 10.1002/adfm.200600384
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Diblock‐Copolymer Micelles for Template‐Based Preparation of PbTiO3 Nanograins

Abstract: A bottom‐up fabrication route for PbTiO3 nanograins grown on predefined TiO2 nanostructures used as seeds is presented. The structuring of the TiO2 seeds is performed using a self‐organized template constructed from a gold‐loaded micellar monofilm. With this fabrication process, TiO2 seeds and PbTiO3 grains with diameters of 12 and 30 nm, respectively, are prepared without the need for electron‐beam lithography. The dimensions of the structure imposed by the micellar template are transferred through all the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 24 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…In particular, it was found that CO dissociation does not occur on the bulk Pt surface. [24] The BET surface area measurement yielded a value of 1.71 m 2 g À1 for PT nanoplates, far lower than that of other oxides. [35][36][37] Even with such a low surface area, the temperature of the 100 % conversion of CO with the Pt/PT nanoplate system remains lower by at least 40 8C than that of Pt/CeO 2 nanocomposites (the 100 % conversion of CO was 144-223 8C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was found that CO dissociation does not occur on the bulk Pt surface. [24] The BET surface area measurement yielded a value of 1.71 m 2 g À1 for PT nanoplates, far lower than that of other oxides. [35][36][37] Even with such a low surface area, the temperature of the 100 % conversion of CO with the Pt/PT nanoplate system remains lower by at least 40 8C than that of Pt/CeO 2 nanocomposites (the 100 % conversion of CO was 144-223 8C).…”
mentioning
confidence: 99%
“…[21] In particular, it has been predicted that CO and NO catalysis could be favored on ultrathin Pt(100) films supported on ferroelectric PbTiO 3 . [22] Various methods have so far been applied to fabricate 0D and 1D ferroelectric nanomaterials, including templated methods, [23][24][25][26] sol-gel processing, [27,28] soft-chemistry routes, [29] solvothermal/hydrothermal reactions, [30,31] and electrospinning techniques. [32,33] Despite much effort, there is still an absence of a simple wet-chemistry method to prepare 2D single-crystal ferroelectric nanomaterials, such as nanoplates and nanodiscs.…”
mentioning
confidence: 99%
“…They have attracted considerable research attention due to their multiple functions as entities of emulsion polymerization [1][2][3] , templates for nanostructure synthesis [4][5][6][7] , and controllable drug delivery [8][9][10][11][12] . Varieties of natural and synthetic amphiphilic molecules and macromolecules have been derived to build micelles for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among them are the high temperature instability of thin films 20 and the use of micro-emulsions 21 or diblockcopolymers. 22 A combination of top-down and bottom-up can also result in well-defined organized nanostructures. Clemens et al for example used electron-beam lithography generated TiO 2 templates as seeds for the formation of PT nanostructures, 23 followed by the deposition of the ferroelectric material by chemical solution deposition, a powerful bottom-up technique.…”
Section: Introductionmentioning
confidence: 99%